In vitro evaluation of antimicrobial effect of Myristica fragrans on common endodontic pathogens - Jyothsna Vittoba Setty; Ila Srinivasan; Roopashree Teeka Sathiesh; Mamata Kale; Vidyullatha Vittoba Shetty; Salgundi Venkatesh (Wolters Kluwer Medknow Publications, 2020)
Background: Complete elimination of microorganisms from the root canals is the important key for the successful endodontic treatment. Constant emergence of resistant strains and adverse effects of synthetic drugs has led to the search of effective herbal alternatives. Nutmeg (Myristica fragrans) is one such spice used for its various medicinal activities. Aims: To evaluate the antimicrobial effect of M. fragrans on common endodontic pathogens of primary tooth. Materials and Methods: Essential oil of nutmeg was extracted by hydrodistillation method, and its phytoconstituents were determined by thin-layer chromatography (TLC), high-performance TLC, and gas chromatography-mass spectrometry analysis. Minimum inhibitory concentration of essential oil against standard strains of common endodontic pathogens (Escherichia coli, Staphylococcus aureus, Enterococcus faecalis, Streptococcus mutans, Candida albicans, Lactobacillus casei, Actinomyces viscosus, Prevotella intermedia, and Porphyromonas gingivalis) was determined by serial tube dilution method. Results: Essential oil of M. fragrans was effective against all tested endodontic microorganisms. Discussion: The active components of essential oil of nutmeg such as myristicin, myristic acid, trimyristin, elemicin, and safrole have good antimicrobial activity and are effective against endodontic microorganisms. Conclusion: M. fragrans can be used as an effective medicament in the treatment of endodontic infections.